Computational Fluid Dynamic (CFD) Analysis to Determine Canard’s Downforce - Muhammad Izzat Nor, Ma'arof; Lavinkumaran, Puvunathan; Wan Zaiyana, Mohd Yusof; Shaheerthana, Suresh; Girma, Tadesse Chala (INTI International University, 2020)
Automotive racing is universally attributed for fast lap time at high speed in a stable car. One of the engineering fits in making this to be possible is via the incorporation of canards at the frontal section of the car which increases the downforce. Such integration of an anti-lift components has omitted the need for electronic intervention. Based on physics, the downforce generated by a canard is directly proportional to its surface area, yet, at the expense of drag force increment. This is of course not desirable since drag force hinders for high speed of travelling. The objective of this study was to determine the downforce generated by two (2) identically designed canards though with varied surface areas via computational fluid dynamic (CFD) analysis for the Alfa Romeo 156. The comparison was made with respect to the surface area versus downforce generated. The CAD model for the canard was developed via Inventor software. Based on the literature, the canards were position at 30-degree angle of attack which is the optimal angle for a canard to function. The results showed that the canard which was 0.38% smaller has successfully generated 21.1% higher downforce and 26.76% less coefficient of lift at 100m/s in comparison to the relatively larger Design 2. Conclusively, a canard could be designed with minimal surface area, thus, with less drag; yet, still managed to provide significant downforce for added stability. For future study, the design used in this study could be used as the benchmark for further improvements.